A cross-age odyssey of cognitive reading attributes: a scoping review - Muhamad Firdaus Mohd Noh; Mohd Effendi Ewan Mohd Matore; Nur Ainil Sulaiman (Frontiers in Psychology)
Reading is a fundamental cognitive-linguistic process that involves the dynamic interaction of multiple interrelated cognitive and perceptual mechanisms. Existing reading models are often limited in fully capturing the intricate relationships between reading attributes across different age groups. This review aims to compare the cognitive attributes utilized in reading assessments for young and adult readers. Using a scoping review methodology, the study analyzed 47 empirical studies selected through a systematic search of reputable academic databases, Scopus, Web of Science, and Google Scholar, from an initial pool of 331 publications. The selection followed a screening process based on three inclusion and exclusion criteria: types of publications, language, and skills assessed. A distinctive pattern emerges in the assessment of cognitive reading skills across age groups, with adult readers evaluated on a wider array of attributes that encompass both fundamental skills and higher order cognitive abilities. In contrast, young readers' assessments tend to center on a narrower spectrum of subskills, primarily emphasizing literal and interpretive comprehension. This developmental pattern calls for the refinement of existing assessment models to better capture the progressive nature of cognitive reading development. Tailoring assessment tools and instructional strategies to align with learners' cognitive demands is imperative for internal stakeholders, while external stakeholders are urged to develop age-appropriate assessments. Future research could address the study's limitations by exploring advanced technologies, such as eye tracking, conducting rigorous reviews, performing cross-linguistic comparative studies, and evaluating diverse assessment methods to enhance the accuracy, effectiveness, and generalizability of reading assessments across various contexts.